Mencipta Sastra Anak Bertema Kearifan Lokal Berbasis Pendidikan Karakter - Rina Ratih (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The concepts of local wisdom inherited through folklores and children literature are the strategies to transform the values considered important to learn by children through textbooks. Therefore, children literature should be meaningful and highly relevant to the empowerment of the children’s life according to the stage of their development. This study questions how to write children’s literature with the theme of local wisdom based on character education. Based on the problem, the study aims to produce children literature with the theme of local wisdom, which is based on character education and according to the children’s development. There are three stages of children literature: emotional, intellectual, and personal development. The study belongs to descriptive qualitative research, employing Brady’s theory on children development and Rampan’s on the technique of writing children literature. Library research and creative process are used in the method. The study generates three models of folklore with the theme of local wisdom according to the children development: Putri Emas dan Burung Ajaib, Putri Cantik dari Pulau Bintan, and Sang Pembangkang. Besides, it also produces three literary works based on character education: “Lalang dan Kupu-Kupu yang Menawan,” “Gara-gara Ketinggalan Bekal,” and “Surti, Mawar, and Kupu-kupu.”